Competency Requirement for Effective BIM Modeller in Design Phase of a Construction Project - Hasan, Ahmad Shawqee; Sarpin, Norliana; Omar, Roshartini; Mohamed, Sulzakimin; Yahya, Mohd Yamani (International Journal of Integrated Engineering, 2021)
Building Information Modelling (BIM) technology has been well received by the Malaysian construction industry, yet the adoption is still in stage 2. Malaysian construction industry is still in implementation of CAD to BIM in design phase. The competency of BIM Modeller in fully utilising BIM is still lacking and this has curtailed the usage of BIM during design phase. According to CIDB, in order to adopt BIM, organisations need to invest in BIM tools such as BIM modeller course. Therefore, the objectives of this study were to identify the benefits of competency among BIM modeller during design phase, to determine the competency needed by BIM modeller and to propose recommendation to improve BIM modeller competency during design phase. The primary data were collected from interview with 4 BIM Modeller to achieve the first and third objectives and subsequently, the second objective was achieved based on 40 received questionnaires from BIM modeller. The data analysis method used are content analysis and descriptive analysis. The results show that all respondents agreed that growing awareness, improve design, shorten timescale and reduce cost are benefits of competency among BIM modeller. The competency that important are including ability to manipulate, navigate and review a 3D model and knowledge of BIM authoring tools. Meanwhile, a few recommendations including BIM training among worker, tactical development, enhance effective collaboration, capabilities of maintaining exchanged data and mobilizing client on importance of BIM are all agreed. The competency of BIM modeller are significant in a project to improve the project design quality. It is hoped that the findings of this study could be useful as a reference to give awareness of construction industry stakeholders towards the importance of BIM modeller competency. It also can be a guide for government and other parties to improve BIM competency level for BIM modeller.